Pengenalan Penggunaan Spektrofotometer UV-Vis untuk Analisis Bahan Pewarna Tekstil Rhodamin B pada Makanan di Lingkungan Sekolah - Anwar, Yelfi; Fathur Rahman; Ruminah; Sari, Sintya Puspita; Ance Tenouye; Akifah, Hana Tri; Ni’am, Laelatun; Riska rahmadani; Dhea Setyalova Wibawanto; Nurul Diniah; Lily Suciati; Agnes Lenoera; Eka Syafitri Puspita S; Ayunda Fajarni Rahmi; Wd Windi Pratiwi (Jurnal Mitra Pengabdian Farmasi, 2022)
The use of textile dyes in food has been a problem for a long time in Indonesia, one of which is textile dyes such as Rhodamine B or Methanol Yellow. The lack of knowledge of school children is a problem where repeated exposure to textile dyes contained in food will become a poison which, if not watched out for, will become a serious problem. Various diseases can arise with repeated exposure to toxic substances and can cause changes in the properties of the body's cells which can lead to malignancy and death. Even though there are synthetic dyes that are safe for food, people still use hazardous materials as food coloring for reasons that end up making big profits in food products that are made and sold, especially in the school environment. The content of Rhodamine B can be determined by UV-Vis Spectrophotometry. It was introduced to students so that school students know that there is a way to test for suspected use of dangerous dyes in the food being sold. The level of knowledge of school students was tested to compare the results before and after participating in counseling on the UV-Vis Spectrophotometer tool. The results of the Paired test show a significant number between the pre-test and post-test values, with a significance value (2-tailed) 0.000 <0.05 indicating a significant difference between the pre-test and post-test, which means there is a difference of Student knowledge which is very significant between before and after counseling about UV-Vis spectrophotometer analysis of Rhodamine B textile dyes in food.